THE EXISTENCE OF CATEGORY SHIFTS IN BILINGUAL HISTORY TEXTBOOK FOR JHS YEAR VII - Anni Niswah Ulul Azmi; Januarius Mujiyanto (JELLT (Journal of English Language and Literature Teaching), 2021)
The definition of shift is a moving or departure from one grammatical system of the source language to another grammatical system in the target language without changing the meaning of it. There are two main types of shifts in translation, level shifts and category shifts. This study attempted to describe the existence of shifts especially category shifts only of words, phrases, clauses, and sentences from the English version to the Indonesian version of the translation of the bilingual book entitled “History Bilingual Textbook for Junior High School Year VII” published by Yrama Widya. I used a descriptive qualitative method as a research design in the process of analysis. I analyzed the category shifts occurred in words by words, phrases by phrases, clauses by clauses, and sentences by sentences carefully. The study found out that the category shifts occurred in the all of the chapters of the textbook consisted of structure, unit, class, and intra-system shift in words, phrases, clauses, and sentences. From the analysis of the study, I can conclude that the category shifts that occurred in the process of textbook translation happened because of four reasons. First, there were grammatical changes specifically in the order of the words. Second, the source texts that located in the different ranks of the unit. Third, the source text that located in the different classes or parts of speech. Fourth, the plural source texts that mostly translated into singular nouns in the target texts.